Knowledge Management Strengthening Character of Entrepreneurs Students Department of Technopreneur at School of Technopreneur Nusantara - Luthfia Fauzia Dewi Aryanti; R. Achmad Rachmat S; Euis Nurninawati; Dedy Prasetya Kristiadi (IJISTECH (International Journal of Information System and Technology), 2022)
This study aims to improve the entrepreneurial character of STMIC Kuwera students with the knowledge management method. The application of knowledge management with an emphasis on strengthening the character of web-based entrepreneurs is expected to be a solution for the character education needs of STMIC Kuwera students to open up job opportunities for the business world by using technology according to their fields. This research will develop a knowledge management system model and design a prototype of the model developed on entrepreneurial character to be packaged as teaching materials for teachers for students. The methodology used is to perform a contingency factor analysis to obtain the knowledge management system model. The resulting knowledge management system model supports the Socialization, Externalization, Combination, Internalization (SECI) process.